Blood trail - Logan, Jake (New York Berkley Books, 1994)
Color illustration on front cover of three superimposed vignettes: head and neck portrait of man wearing brown western hat and red bandana; man wearing blue shirt and black pants embracing woman wearing red dress; man and woman crouched behind a rocky outcropping, the man holds a pistol in his proper right hand.
Keywords: Western radio programs -- Western stories -- Slocum (Fictitious character)